Simulation Of Premi Calculation Claims Insurance Base On Web; Case Study PT. Sinarmas Insurance Padang - Rohendi, Keukeu; Putra, Ilham Eka (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2016)
Sinarmas currently has several insurance services featured. To perform its function as a good insurance company is need for reform in terms of services in the process of calculating insurance premiums of insurance carried by marketing to use a calculator which interferes with the activities of marketing activities, slow printing insurance policies, automobile claims process that requires the customer to come to the office ASM, slow printing of Work Order (SPK) and the difficulty recap customer reports. Therefore we need a Design and Development of Information Systems and Process Simulation Premium Calculation new claims-based Web using PHP and MySql centrally at PT. Sinarmas Insurance. So as to provide convenience for customers to know the amount of insurance premiums quickly without having to contact marketing, data management, printing of policies fast, the process claim that does not require the customer to come to the office of ASM and reporting of customer data, customer data management and reporting as well as ensuring the flexibility of information produced.